Global Price Fixing - Connor, John M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
The book describes and analyzes the formation, operation, and impacts of modern global cartels. It provides a broad picture of the economics, competition law and history of international price fixing. A deeper understanding of the phenomenon is afforded by intensive case studies of collusion in the markets for lysine, citric acid, and vitamins. Particular attention is given to the economic injuries sustained by the cartels' customers. The author assesses whether antitrust enforcement by the European Union, the United States, and other countries is capable of deterring cartels in the foreseeable future.
The Economics of Price Fixing -- Anticartel Laws and Enforcement -- The Citric Acid Industry -- The Citric Acid Conspiracy -- Economic Impacts of the Citric Acid Cartel -- The World Lysine Industry -- The Lysine Conspiracy -- Economic Effects of the Lysine Cartel -- The Global Vitamins Industries -- The Vitamins Conspiracies -- Effects of the Vitamins Cartels -- U.S. Government Prosecutions -- Antitrust Prosecutions Outside the United States -- The Civil Suits -- The Business of Fighting Cartels -- Global Price Fixing: Summing Up.
Keywords: Industrial organization; Law and economics; International economics; Industrial Organization; Law and Economics; International Economics